Study on the Laboratory Mixing and Compaction Methodology of Emulsified Asphalt Cold Recycled Mixture - Liu, Liping; Han, Zhanchuang; Wu, Ping; Zheng, Guangshun; Sun, Lijun (Frontiers in Materials, 2020)
Emulsified asphalt cold recycled mixture is commonly used in the upper base course of expressway reconstruction asphalt pavement. When the following layer is paved with hot-mix asphalt (HMA) mixture, the aging asphalt in the recycled material is activated due to the temperature conduction effect of the HMA mixture, so that the cold recycled layer produces “secondary thermal compaction” under the action of a roller. Based on this phenomenon, the present study aimed to discuss the influence of different molding methods and mixing processes on the volume parameters and mechanical properties of cold recycled emulsified asphalt mixture. The influences of Marshall compaction times, gyratory compaction times, curing time, and specimen-forming temperature on the voids and splitting strength of cold recycled mixture were studied. The field core sample was compared with the laboratory-forming method, which accords with the field compaction condition of the cold recycled upper base. first-time compaction number of large Marshall is 150 times and secondary compaction number is 75 times (Shorthand for 150 + 75), the compaction times of the gyratory specimen is “30 + 15.” The curing time of the cold recycled mixture should not exceed 3 h and should not be constructed in low-temperature weather to ensure the quality of pavement construction. The use of a new stage and step laboratory mixing process simulating the plant mixing, compared with the traditional mixing process, increases the splitting strength by at least 13%.